2008
DOI: 10.1007/s11661-007-9451-8
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of Mechanical Properties and Hydrogen Embrittlement Resistance of Austempered vs Quenched and Tempered 4340 Steel

Abstract: This study was conducted to compare the hydrogen embrittlement (HE) resistance of austempered 4340 steel with quenched and tempered (Q&T) 4340 steel with an identical yield strength (YS) of 1340 MPa (194 ksi). A baseline comparison showed that the austempered steel with a lower bainite microstructure exhibited higher hardness, tensile strengths, Charpy V-notch (CVN) impact toughness, and ductility at both low 233 K (-40 F) and ambient temperatures, as compared to the Q&T steel with a martensite microstructure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 8 publications
3
6
0
2
Order By: Relevance
“…For comparison the hardness and charpy impact energy of full martensite and bainite steels are also measured. It can be seen from Table 3 that bainitic steel has greater impact energy and elongation than martensitic steel which is in agreement with the results of Tartaglia et al [6]. They reported that lower bainite is tougher than tempered martensite in AISI 4340 steel.…”
Section: Microstructuresupporting
confidence: 89%
“…For comparison the hardness and charpy impact energy of full martensite and bainite steels are also measured. It can be seen from Table 3 that bainitic steel has greater impact energy and elongation than martensitic steel which is in agreement with the results of Tartaglia et al [6]. They reported that lower bainite is tougher than tempered martensite in AISI 4340 steel.…”
Section: Microstructuresupporting
confidence: 89%
“…Their strength and impact toughness could be further improved by replacing conventional Q&T with austempering, which leads to bainitic or mixed bainite-martensite microstructures [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…After tempering to the same hardness, the ductile-to-brittle impact transition temperature for any carbon level was 25-50°C (45-90°F) lower for fully martensitic microstructures than for microstructures containing only 50% martensite. This author and others have shown that SAE 4340 steel has better impact toughness when it is austempered (isothermally transformed) to 100% lower bainite than when it is quenched to 100% martensite and tempered to the same strength level ( Ref 1,2). However, steels with mixed microstructures resulting from incomplete bainitic treatments and partial transformation to martensite possess much lower toughness (higher transition temperatures) than steels with microstructures containing either 100% lower bainite or 100% tempered martensite ( Ref 1).…”
Section: Introductionmentioning
confidence: 93%